“Vestir A Camisa” da inovação: afeto, instrumento ou norma? comprometimento de equipes de P&D&I e a capacidade de inovação em negócios tradicionais e de impacto social - Ronzani, Célia Maria (2018)
Innovation capacity encompasses an organization’s skill set aimed at mobilizing human, physical, technological and financial resources to bring society something new. In this process, teams that work directly in Research, Development and Innovation (R&D&I) take center stage, as their commitment can be considered a relevant social phenomenon in both theoretical and practical terms, considering the possibility of mobilizing pro-innovation resources, which hone the organizations’ innovation capacity. Additionally, it is a multilayered phenomenon with regards to traditional and social businesses’ scopes of operation. In light of this context, the following question was raised: how can the commitment of R&D&I teams contribute towards mobilizing resources that foster traditional business (TB) and social business’ (SB) innovation capacity? This qualitative-descriptive research adopted the multiple-case study method, and its units of analysis are: a traditional business, BRAILE, winner of the “FINEP (Innovation Studies and Projects Finance Company)” award in the Medium Company category; and a social business, CREN, recipient of Folha de S. Paulo’s “Social Entrepreneur” award. Data was gathered from semi-structured interviews (14) and document surveys (2). The field study generated 10.5 hours of recordings and a 114-page transcription, in addition to two pages of evidence obtained from documental research. The data was interpreted by means of content analysis, with the help of the Atlas Ti. software, which was used to organize and code the data. From the combined analysis of results, it was possible to validate the primary proposition that the innovation capacity and the R&D&I teams’ (main categories analyzed) affective commitment were crucial to set apart the traditional business investigated (BRAILE), as they boosted the development of technological innovations with frugal characteristics. These categories were also important for the social business investigated (CREN), promoting social value and, consequently, social innovations. It was also possible to validate the secondary proposition that people management and the TB and SB’s strategic fundaments (secondary categories analyzed) have an effect on the internal mobilization of pro-innovation resources and, consequently, stimulated the R&D&I teams’ affective commitment, enhancing the exchange of tacit and explicit knowledge and also the generation of innovation to the market and society. This way, we were able to propose a framework for what commitment, innovation capacity, strategic fundaments and people management stand for, highlighting the differences and similarities between traditional and social businesses.